2020
DOI: 10.1097/01.naj.0000718624.25806.3f
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Suicide Among RNs: An Analysis of 2015 Data from the National Violent Death Reporting System

Abstract: Academia (new graduates entering occupation/specialty) All other (total population) Demand for Health Workers By occupation/specialty and setting Physicians  Advance practice nurses  Physician assistants  Nurses  Oral health  Behavioral health  Rehabilitation  Pharmacy  Respiratory care  Therapy  Dietary and nutrition  Diagnostic laboratory  Diagnostic imaging  Vision and hearing  Direct care professions Criminal Justice System

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…One report with a large sample of nurses from 1982 to 1996 found no difference in suicide incidence vs the general population; however, another study that used 1990 data found an increased risk . More recent studies report a relative difference when comparing nurses with the general population . For instance, using 2014 NVDRS data, Davidson and colleagues reported the RR of suicide among female nurses vs the general population to be 1.58 (95% CI, 1.34-1.85).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One report with a large sample of nurses from 1982 to 1996 found no difference in suicide incidence vs the general population; however, another study that used 1990 data found an increased risk . More recent studies report a relative difference when comparing nurses with the general population . For instance, using 2014 NVDRS data, Davidson and colleagues reported the RR of suicide among female nurses vs the general population to be 1.58 (95% CI, 1.34-1.85).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, less is known about suicide among nurses. Although nursing is the largest health care profession (3.3 million nurses in the US), there are very few empirical studies of suicide among US nurses, too few to be included in a recent meta-analysis . However, recent studies found that the incidence of suicide among nurses is higher than that in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Within the United States, the incidence of nurse suicide has been studied by 3 different research teams 4,6,7 using data collected by the Centers for Disease Control and Prevention (CDC) in the National Violent Death Reporting System (NVDRS) restricted database. 8 Each team used a different analytical approach but reported the same result: nurses are at a higher risk of suicide in the United States than in the general population, adjusting for age and gender (see Supplemental Digital Content, available at: http: //links.lww.com/NAQ/A10).…”
Section: Nurse Suicidementioning
confidence: 99%
“… 22 Nurses appear to be at higher risk for suicide than both physicians and the general public. 24 , 25 …”
mentioning
confidence: 99%